Communication between the median nerve and the musculocutaneous nerve: Occurrence and significance - B N Shruthi; Shreya Krishnamurthy; K Ruthvik; B Rahul (Wolters Kluwer Medknow Publications, 2020)
Background: The median nerve and musculocutaneous nerve are nerves arising from the brachial plexus supplying the muscles of the arm and forearm. The communication between these nerves is of clinical importance in the traumatology of the shoulder joint and upper arm and in situations where a surgeon needs to isolate and trace the median and musculocutaneous nerves distally. Aims and objectives: The study was conducted to observe and discuss the communications between the median and musculocutaneous nerves. The data was statistically analysed. Materials and Methods: The present study was conducted on 60 cadaveric upper limbs (left: right=30:30) obtained from the department of Anatomy, Rajarajeswari Medical College and Hospital, Bengaluru. The brachial plexus was dissected according to standard dissection procedures and the median nerve and musculocutaneous nerve were exposed. Results: The musculocutaneous nerve did not pierce the coracobrachialis in 5 limbs. However, the nerve did supply the coracobrachialis muscle in all cases. In 5 upper limbs (8.3%), a single communicating nerve was observed between the median nerve and the musculocutaneous nerve. In one case (1.67%), two communicating nerves were observed between the median nerve and the musculocutaneous nerve. Conclusion: Variations in the formation and branching of the brachial plexus have been reported by several researchers. The anatomical variations of musculocutaneous nerve and median nerve are important to neurosurgeons ,orthopaedicians and general surgeons who deal with cases of neurofibromatosis and neurotization procedures. Surgeons must consider the possible presence of the communication between the median nerve and musculocutaneous nerve in such cases.